Relationship Between Position and Work Duration with Suspect Carpal Tunnel Syndrome in Maxim Online motorcycle taxi at Makassar - -, Marfuah Nawawi; Putri, Melda; Mustari, Yery (Nusantara Medical Science Journal, 2023)
Introduction: Online motorcycle taxi is a service that is currently widely used in goods delivery services and other forms of services. There are several things that are not considered by online motorcycle taxi drivers when driving, namely the driving position that is not good and correct. The more consumer demand for online motorcycle taxi applications, the higher the working hours of online motorcycle taxi drivers which leads to increased complaints of pain in the body. This study aims to determine the relationship between position and duration of work with complaints of suspected carpal tunnel syndrome in maxim motorcycle taxi drivers in Makassar City. Methods: The sampling technique in this study was purposive sampling through a cross sectional approach. Respondents in this study were riders aged 17 years and over as many as 373 riders who met the exclusion and inclusion criteria. Work position was measured using REBA, Work Duration was measured using a work duration questionnaire, while Suspect carpal tunnel syndrome complaints were measured using Phalen's Test. Results: The Kolmogorov Smirnov normality test shows a significance value (p) of 0.000, meaning that the data is not normally distributed (p <0.05). Then the correlation test between the two variables using the Spearman's rho test (p), namely the work position with complaints of suspected carpal tunnel syndrome obtained results (p=0.025; r=0.116 *) which means there is a significant relationship between the two variables and for the duration of work with complaints of suspected carpal tunnel syndrome obtained results (p=0.448; r=0.39) which means there is no relationship between the two variables. Conclusions: The distribution of maxim online motorcycle taxi drivers' work positions in the city of Makassar is dominated by respondents who experience the high risk category and category of work duration are more than 8 hours/day. There is a significant relationship between work position and complaints of suspected carpal tunnel syndrome on maxim online motorbike taxis in the city of Makassar. There is no significant relationship between work duration and complaints suspect carpal tunnel syndrome on maxim online motorcycle taxi in Makassar city.